Assessing the level of awareness and vaccination status of Hepatitis B among young female community of Pakistan (Bangladesh Journal of Medical Science, 2015)
Objectives: Hepatitis B virus (HBV) infection is a global health problem with about 2 billion infected persons. Pakistan is one of the endemic areas for viral hepatitis B. Prevention is merely a safe approach rather than curing against high incidence of viral hepatitis. Therefore, the aim of the present study was to assess the knowledge and awareness of HBV infection, its prevention and transmission, perception of HBV vaccine and vaccination status among young females of Karachi, Pakistan. Methods: This cross sectional study was conducted from Oct till Dec 2014 by adopting a pre-validated questionnaire distributed to female individuals in Karachi, Pakistan. Descriptive statistics were used to demonstrate students demographic information and their response to the questionnaire items. Kruskal Wallis H test was executed to evaluate the association of age and educational status of the respondents with their response. A p-value